2019
DOI: 10.1097/bco.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

Middle third clavicular fractures fixed with precontoured locking compression plate or reconstruction plate: comparison of outcomes and complications

Abstract: Background: Fractures of the clavicle account for 2.6% to 4% of all fractures. Operative management of displaced fractures of the midshaft clavicle is preferred due to better outcomes. Various plates are used for fixation of these fractures, which include reconstruction plates, dynamic compression plates, and precontoured locking plates. Very few studies have documented whether the proposed benefits of precontoured plates are realized in a clinical setting. In this study, we compared the outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Concerning superior locking plates, 23 studies were identified. 1 , 2 , 4 , 9 , 10 , 12 , 13 , 17 , 19 , 20 , 24 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 63 , 66 , 76 The average patient age from all studies was 37.8 years (range 17-79) with mean length of follow-up of 29.3 months. Five studies reported a Constant-Murley Score (CMS) 14 at 6 months, 1 of these studies did not include a standard error.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning superior locking plates, 23 studies were identified. 1 , 2 , 4 , 9 , 10 , 12 , 13 , 17 , 19 , 20 , 24 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 63 , 66 , 76 The average patient age from all studies was 37.8 years (range 17-79) with mean length of follow-up of 29.3 months. Five studies reported a Constant-Murley Score (CMS) 14 at 6 months, 1 of these studies did not include a standard error.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported a Constant-Murley Score (CMS) 14 at 6 months, 1 of these studies did not include a standard error. 20 , 35 , 36 , 57 , 66 Four studies reported CMS scores at 12 months, 1 of these did not report standard errors. 36 , 40 , 57 Four studies reported DASH 28 scores at 12 months of which 1 study did not report standard errors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations